2016
DOI: 10.21037/atm.2016.07.06
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of myocardial ischemia

Abstract: Over the last 60 years, echocardiography has emerged as a dominant and indispensable technique for the detection and assessment of coronary heart disease (CHD). In this review, we will describe and discuss this powerful tool of cardiology, especially in the hands of an experienced user, with a focus on myocardial ischemia.Technical development is still on-going, and various new ultrasound techniques have been established in the field of echocardiography in the last several years, including tissue Doppler imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Echocardiography has a central role in the diagnosis and risk stratification of acute myocardial infarction (MI) patients [5]. Newer techniques, such as tissue Doppler imaging and speckle tracking echocardiography, have emerged as valuable diagnostic and prognostic tools in patients with acute coronary syndrome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiography has a central role in the diagnosis and risk stratification of acute myocardial infarction (MI) patients [5]. Newer techniques, such as tissue Doppler imaging and speckle tracking echocardiography, have emerged as valuable diagnostic and prognostic tools in patients with acute coronary syndrome [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, condition of LV remodeling could be used as a predictive factor for mortality and morbidity in patients with MI [ 7 ]. Electrocardiography (ECG) has become the most commonly used technique for the assessment of heart disease [ 8 ]. Wang et al reported that the use of the ECG score system was the best diagnositic tool in the estimation of ischemia conditions with quantitative analysis of change in the ST-segments for either anterior or inferior LV [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…If conservative therapy does not improve DO 2 , mechanical support and/or implantation of a left ventricular microaxial pump may be discussed. Lastly, if (new) regional wall motion abnormalities are detected, specifically LV wall hypokinesia, akinesia or dyskinesia [ 82 ], this may hint at specific cause such as myocardial infarction or Takotsubo syndrome, which require specific diagnostic testing (e.g. electrocardiogram, cardiac enzymes, coronary angiography) and treatment.…”
Section: Main Textmentioning
confidence: 99%